Shipyard manpower digital recruitment: A data-driven approach for Norwegian stakeholders - Bogdan Florian Socoliuc; Andrei Alexandru Suciu; Mădălina Ecaterina Popescu; Doru Alexandru Plesea; Florin Nicolae (Economies, 2025)
This study examines the effectiveness of digital recruitment platforms in addressing labor shortages within Norway's shipbuilding and ship-repair industry. Through a data analysis of 446 job applications over a 12-month period, this study evaluates key recruitment metrics, including application response times (ARTs), candidate acceptance rates (CARs), and the impact of machine learning on hiring outcomes. The findings reveal that specialized digital platforms can significantly improve recruitment efficiency, with 70% of applications being received within 24 h, highlighting the platforms's great potential for time-sensitive sectors. Additionally, pre-vetting candidates enhances hiring precision, achieving a CAR of 90% and reducing mismatches. The application of machine learning algorithms provides predictive insights that support real-time adjustments to job postings, optimizing recruitment strategies. This study contributes uniquely to the literature on cross-border digital recruitment, aligning with the European Union goals of sustainable labor mobility and economic resilience.
Keywords: 330; digital recruitment; labor mobility; labor shortages; Norway shipyards; maritime industry